A Material View on Extrinsic Magnetic Domain Wall Pinning in Cylindrical CoNi Nanowires - Schöbitz, Michael; Novotný, Ondrej; Trapp, Beatrix; Bochmann, Sebastian; Cagnon, Laurent; Thirion, Christophe; Massebœuf, Aurélien; Mossang, Eric; Fruchart, Olivier; Bachmann, Julien (Journal of Physical Chemistry C, 2023)
Speed and reliability of magnetic domain wall (DW) motion are key parameters that must be controlled to realize the full potential of DW-based magnetic devices for logic and memory applications. A major hindrance to this is extrinsic DW pinning at specific sites related to shape and material defects, which may be present even if the sample synthesis is well controlled. Understanding the origin of DW pinning and reducing it are especially desirable in electrochemically deposited cylindrical magnetic nanowires (NWs), for which measurements of the fascinating physics predicted by theoretical computation have been inhibited by significant pinning. We experimentally investigate DW pinning in CoxNi100-x NWs by applying quasi-static magnetic fields. Wire compositions were varied with x = 20, 30, and 40, while the microstructure was changed by annealing or by varying the pH of the electrolyte for deposition. We conclude that pinning due to grain boundaries is the dominant mechanism, decreasing inversely with both the spontaneous magnetization and grain size. Second-order effects include inhomogeneities in lattice strain and the residual magnetocrystalline anisotropy. Surface roughness, dislocations, and impurities are not expected to play a significant role in DW pinning in these wire samples.
CRIS-Team Scopus Importer:2023-02-24